MARDI’s use of 4P marketing mix strategy for rare fruits planting material - Mohd Norfaizal Ghazalli (2022)
Planting materials of rare fruits have a unique market which is also known as a niche market. The lack of consumer comprehension about the nutritional value of rare fruits is one of the factors contributing to low consumer demand. Promotion is a very important activity to ensure a developed product reaches its target audience. Therefore, MARDI through the Gene Bank and Seed Centre have used several promotional methods to increase consumer awareness and thus increasing demand for rare fruit planting materials. This study is conducted to survey marketing strategies based on the 4Ps strategy, namely, Product, Price, Place and Promotion. MARDI’s planting materials effectively practiced the 4P marketing mix strategy. The sale of rare fruit plants from 2012 to 2016 increased twice its base value generated from sales in events and sales at MARDI’s Gene Bank and Seed Centre. Promotion is done through major agriculture exhibitions including Hari Peladang, Penternak dan Nelayan Kebangsaan, Malaysian Agriculture, Horticulture and Agrotourism Show (MAHA) and state carnivals. However, the marketing strategies need to be improved to satisfy the needs of consumers and to compete with other nurseries.